Silicone Hydrogel and Rigid Gas-Permeable Scleral Lens Tear Exchange. Issue 2 (March 2018) - Paugh, Jerry R.; Chen, Elaine; Heinrich, Colton; Miller, Heidi; Gates, Tiffany; Nguyen, Andrew Loc; Edrington, Timothy; Weissman, Barry A.
Abstract : Objectives: To quantify tear elimination rate (ER) underneath silicone hydrogel (Si-Hy) and scleral gas permeable (GP) contact lenses (CLs). Methods: Subjects successfully using either well-fitting soft Si-Hy CLs or scleral GP CLs were recruited. Most scleral GP CL wearers had irregular corneas (e.g., keratoconus). An objective fluorometer measured decay of fluorescein isothiocyanate dextran dye signal (70 kD MW) from which the tear ER in %/min was calculated. For GP scleral lenses, the ER was determined for both the initial settling period and the 30- to 60-min period, and without lenses. All ERs were calculated from 5 to 30 min to avoid reflex tearing effects. Results: Fourteen soft Si-Hy CL and 12 scleral GP CL wearers completed the study. The ER for the scleral GP CL wearers averaged 0.57 (±0.6) %/min for the 0- to 30-min and 0.42 (±0.5) %/min for the 30- to 60-min period ( P =0.515). Non-CL wear tear ER in these same subjects averaged 34.17 (±15.9) %/min and was significantly different versus both scleral GP wear periods (both P values <0.001). The ER for the soft Si-Hy CL wearers, 5 to 30 min, averaged 6.09 (±2.8) %/min. Conclusions: Our data demonstrate significantly less ER in well-fit scleral GP CL wearers compared with soft Si-Hy CL wearers for both the settling and longer wear periods (both P values <0.001). Moreover, slightly greater tear exchange was observed during the scleral GP CL settling period than later, which may reflect a change over time in tear vault thickness.